2007
DOI: 10.1016/j.adolescence.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Depression and school performance in middle adolescent boys and girls

Abstract: The study aimed to investigate the associations between different levels of depression with different aspects of school performance. The target population included 2516 7th–9th grade pupils (13–17 years) of whom 90% completed the questionnaire anonymously in the classroom. Of the girls 18.4% and of the boys 11.1% were classified as being depressed (R‐Beck Depression Inventory (BDI), the Finnish version of the 13‐item BDI). The lower the self‐reported grade point average (GPA) or the more the GPA had declined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
204
5
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(251 citation statements)
references
References 33 publications
23
204
5
13
Order By: Relevance
“…Nevertheless, the specific age when this difference begins is controversial and other factors associated with depressive symptoms among adolescence seems to vary among different population [32,33]. The World health Organization [34] stated that depression is the leading cause of disability with a 50% higher rate of burden of depression among women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the specific age when this difference begins is controversial and other factors associated with depressive symptoms among adolescence seems to vary among different population [32,33]. The World health Organization [34] stated that depression is the leading cause of disability with a 50% higher rate of burden of depression among women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies have indicated that internalizing symptoms impair academic achievement (Brackney & Karabenick, 1995;Fröjd et al, 2008;Malinauskiene, Vosylis, & Zukauskiene, 2011;Pekrun, Goetz, Titz, & Perry, 2002;Roeser, Eccles, & Sameroff, 1998;Tesiny, Lefkowitz, & Gordon, 1980;Thornberry, Ireland, & Smith, 2001;Woodward & Fergusson, 2001). In contrast, other reports have suggested that there is no direct relationship between internalizing problems and academic performance (Barriga et al, 2002;Strauss, Lahey, & Jacobsen, 1982) and that psychopathology influences academic achievement only indirectly, through its determinants, such as motivation, self-efficacy and resource-management (Brackney et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, this has been shown to be beneficial for vulnerable young people (Borup & Holstein, 2004). In general, a stronger focus on health promotion in school could not only enhance the young people’s health but also improve their learning (Ahonen, 2010; Fröjd et al, 2008). In addition, the young people in this study expressed a need to be listened to and to be treated as individuals (in relation to social services and contact with adults).…”
Section: Discussionmentioning
confidence: 99%